Risk of excavators overturning: Determining horizontal centrifugal force when slewing freely suspended loads. Issue 3 (15th April 2019) - Edwards, David; Parn, Erika A.; Sing, Michael C.P.; Thwala, Wellington Didibhuku
Abstract : Purpose: Tracked hydraulic excavators are versatile and ubiquitous items of off-highway plant and machinery that are utilised throughout the construction industry. Each year, a significant number of excavators overturn whilst conducting a lifting operation, causing damage to property, personnel injury or even fatality. The reasons for the overturn are myriad, including: operational or environmental conditions; machine operator acts or omissions; and/or inadequate site supervision. Furthermore, the safe working load (SWL) figure obtained from manufacturer guidance and utilised in lift plans is based upon undertaking a static load only. The purpose of this paper is to determine whether the SWL is still safe to be used in a lift plan when slewing a freely suspended (dynamic) load, and, if not, whether this may be a further contributory factor to overturn incidents. Design/methodology/approach: Previous research has developed a number of machine stability test regimes but these were largely subjective, impractical to replicate and failed to accurately measure the "dynamic" horizontal centrifugal force resulting from slewing the load. This research contributes towards resolving the stability problem by critically evaluating existing governing standards and legislation, investigating case studies of excavator overturn and simulating the dynamic effects of an excavator when slewing a freely suspended load at high rotations per minute (rpm). To achieve this, both the static load and horizontal centrifugal force from slewing this load were calculated for six randomly selected cases of an excavator, with different arm geometry configurations. Findings: The results from the six cases are presented and a worked example of one is detailed to demonstrate how the results were derived. The findings reveal that the SWL quoted on an excavator's lift rating chart considerably underestimates the extra forces experienced by the machine when an additional dynamic load is added to the static load whilst lifting and slewing a freely suspended load. Originality/value: This work presents the first attempt to accurately model excavator stability by taking consideration of the dynamic forces caused by slewing a freely suspended load and will lead to changes in the way that industry develops and manages lift plans. Future research proposes to vary the weight of load, arm geometry and rpm to predict machine stability characteristics under various operational conditions, and exploit these modelling data to populate pre-programmed sensor-based technology to monitor stability in real time and automatically restrict lift mode operations.